The plant cytoskeleton - Liu, Bo (Springer New York, 2011)
Plant cells house highly dynamic cytoskeletal networks of microtubules and actin microfilaments. They constantly undergo remodeling to fulfill their roles in supporting cell division, enlargement, and differentiation. Following early studies on structural aspects of the networks, recent breakthroughs have connected them with more and more intracellular events essential for plant growth and development. Advanced technologies in cell biology (live-cell imaging in particular), molecular genetics, genomics, and proteomics have revolutionized this field of study. Stories summarized in this book may inspire enthusiastic scientists to pursue new directions toward understanding functions of the plant cytoskeleton. The Plant Cytoskeleton is divided into three sections: 1) Molecular Basis of the Plant Cytoskeleton; 2) Cytoskeletal Reorganization in Plant Cell Division; and 3) The Cytoskeleton in Plant Growth and Development. This book is aimed at serving as a resource for anyone who wishes to learn about the plant cytoskeleton beyond ordinary textbooks. Bo Liu is professor in the Department of Plant Biology at the University of California in Davis, California. He received his B.S. degree in cell biology and genetics and M.S. degree in cell biology from Peking University in Beijing, China, and Ph.D. degree in botany from the University of Georgia in Athens, Georgia. Research in his laboratory is focused on studying the cytoskeletal basis of intracellular motility in flowering plants and filamentous fungi.